O perfil do empreendedorismo da zona norte de Mossoró-RN e sua relação com a consciência ambiental - Avelino, Arthur Ericlis de Oliveira (Universidade Federal Rural do Semi-Árido, 2019)
The present project aims to outline the profile of the entrepreneurs working in the northern area of Mossoró-RN and verify the environmental awareness of the managers / owners. Bringing the concept of entrepreneurship, a sustainability approach and a definition of environmental awareness, making use of the quantitative analysis and the descriptive method, from the data obtained by a questionnaire to analyze the profile of the local entrepreneurs of the project by Maristelio Cruz, and another questionnaire to measure the environmental awareness of the respondents of Otto, Silva and Silveira-Martins (2017), who obtained a return of 43 commercial establishments in the Santo Antônio neighborhood in the northern area of Mossoró-RN, where it was verified that the managers / owners of the companies questioned are aware of their responsibilities to the environment and to society.
Monografia
Keywords: Consciência ambiental; Sustentabilidade; Perfil empreendedor; Empreendedores; Environmental awareness; Sustainability; Profile entrepreneur; Entrepreneurs; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA